Use of Google Trends to investigate loss‐of‐smell‒related searches during the COVID‐19 outbreak. Issue 7 (15th June 2020) - Walker, Abigail; Hopkins, Claire; Surda, Pavol
Abstract : Background: Initial reports describing coronavirus 2019 (COVID‐19) were dominated by the presence of cough, breathlessness, and fever; anecdotal reports suggested anosmia may also be a manifestation. We used Google Trends (GT) to investigate whether there was a surge in individuals searching for information related to smell loss during the COVID‐19 epidemic in Italy, Spain, the United Kingdom, the United States, Germany, France, Iran, and The Netherlands. Methods: GT was used to explore internet activity related to loss of smell in the 8 aforementioned countries. Spearman rank analysis was performed to correlate loss‐of‐smell‒relative search volumes (RSVs), with the increases of daily confirmed cases of COVID‐19 and deaths attributed to disease. As a control event, we also performed analysis of smell‐related searches during the last UK influenza epidemic of 2009. Results: In all 8 countries, we observed strong correlations between daily RSVs related to loss of smell, increases of daily COVID‐19 + cases and deaths ranging from 0.633 to 0.952. All correlations were statistically significant ( p < 0.05). Conclusion: There is a strong correlation between the frequency of searches for smell‐related information and the onset of COVID‐19 infection in Italy, Spain, UK, USA, Germany, France, Iran, and The Netherlands. We hypothesize this may relate to a previously underrecognized symptom.